Serum Uric Acid-to-Serum Creatinine Ratio, Thyroid Function, and Gestational Diabetes Mellitus Risk during Early Pregnancy among Chinese Women - Song S; Duo Y; Zhang Y; Qiao X; Chen Y; Fu Y; Dong Y; Yuan T; Zhao W (Diabetes, Metabolic Syndrome and Obesity, 2025)
Shuoning Song,1 Yanbei Duo,1 Yuemei Zhang,2 Xiaoli Qiao,3 Yan Chen,3 Yong Fu,1 Yingyue Dong,1 Tao Yuan,1 Weigang Zhao1 1Department of Endocrinology, Key Laboratory of Endocrinology of Ministry of Health, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Obstetrics, Haidian District Maternal and Child Health Care Hospital, Beijing, People’s Republic of China; 3Department of Obstetrics, Beijing Chaoyang District Maternal and Child Health Care Hospital, Beijing, People’s Republic of ChinaCorrespondence: Tao Yuan, Email yuantao@pumch.cn; t75y@sina.com Weigang Zhao, Email xiehezhaoweigang@163.comObjective: This study aimed to explore the relationship between serum uric acid-to-serum creatinine (UA:SCr) ratio and thyroid function within the normal range and in gestational diabetes mellitus (GDM) during early pregnancy in Chinese women.Methods: A total of 958 pregnant women were enrolled in this prospective double-center cohort study. Liver function, renal function, and thyroid function were tested during 6– 12 weeks of gestation and oral glucose tolerance tests were conducted for 24– 28 weeks to screen for GDM. Associations between UA:SCr ratio and thyroid function and GDM were examined by linear and logistic regression analyses.Results: The incidence of GDM was 19.3% (185/958) in this study. UA:SCr ratio and free thyroxine (FT4) were significantly higher in pregnant women with GDM in the highest preBMI quartile than the normal glucose tolerance group (median 5.22, IQR 4.47– 5.87 vs median 4.87, IQR 4.05– 5.61, mean difference − 0.52, P=0.04; median 1.13, IQR 1.02– 1.28 vs median 1.18, IQR 1.07– 1.32, mean difference 0.14, P=0.02). Both UA:SCr ratio and FT4 were associated with risk of GDM in pregnant women in the highest preBMI quartile (RR 0.331, 95% CI 1.094– 1.772, P=0.007; RR − 1.533, 95% CI 0.055– 0.853, P=0.029). For pregnant women in the third and fourth preBMI quartiles, the UA:SCr ratio was significantly correlated with euthyroid function (FT4 and UA:SCr ratio): preBMI quartile 3 — β=0.659, 95% CI 0.231– 1.087), P=0.003; FT4 and UA:SCr ratio in preBMI quartile 4 — β=− 0.263, 95% CI − 0.516 to− 0.011, P=0.041; TSH and UA:SCr ratio in preBMI-quartile 4 — β=0.131, 95% CI 0.008– 0.253, P=0.036. Further analysis revealed that FT4 was associated with risk of GDM in pregnant women in the highest UA:SCr ratio quartile (RR 0.052, 95% CI 1.010– 1.096, P=0.012). There was also an interaction effect between FT4 and UA:SCr ratio in relation to the risk of GDM in the highest UA:SCr ratio quartile (P=0.02).Conclusion: Both UA:SCr ratio and FT4 were associated with the risk of GDM in early pregnancy, particularly among women in the highest prepregnancy BMI quartile. FT4 level within the normal range was correlated with UA:SCr ratio in women in the third and fourth prepregnancy BMI quartiles. These results suggest the complex interplay of metabolic changes during early pregnancy and provide new insights for the early prevention and management of GDM.Keywords: pregnancy, uric acid, thyroid function, gestational diabetes mellitus, glucose and lipid metabolism